2000
DOI: 10.1021/np000219r
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Synthesis, and Structure−Activity Relationships of Bioactive Benzoquinones from Miconia lepidota from the Suriname Rainforest

Abstract: Bioactivity-directed fractionation of an EtOAc extract from the leaves of Miconia lepidota afforded the two benzoquinones 2-methoxy-6-heptyl-1,4-benzoquinone (1) and 2-methoxy-6-pentyl-1,4-benzoquinone (primin) (2). This is the first reported isolation of 1. Both quinones 1 and 2 exhibited activity toward mutant yeast strains based on Saccharomyces cerevisiae, indicative of their cytotoxicity and potential anticancer activity. A number of previously synthesized and new analogues were prepared and tested in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 9 publications
0
43
0
3
Order By: Relevance
“…Previous studies on Miconia species have demonstrated the presence of triterpenes, coumarins, and benzoquinones in these plants (Chan et al, 1992;Gunatilaka et al, 2001;Lowry, 1968;Macari et al, 1990). In recent work undertaken in our laboratory, several crude plant extracts from Miconia and their isolated compounds were reported to exhibit remarkable biological activities Resende et al, 2006;Spessoto et al, 2003;Vasconcelos et al, 2006).…”
Section: Introductionmentioning
confidence: 89%
“…Previous studies on Miconia species have demonstrated the presence of triterpenes, coumarins, and benzoquinones in these plants (Chan et al, 1992;Gunatilaka et al, 2001;Lowry, 1968;Macari et al, 1990). In recent work undertaken in our laboratory, several crude plant extracts from Miconia and their isolated compounds were reported to exhibit remarkable biological activities Resende et al, 2006;Spessoto et al, 2003;Vasconcelos et al, 2006).…”
Section: Introductionmentioning
confidence: 89%
“…189 A convergent general synthesis of annelated quinones and highly substituted quinones (149-151) from conjugated ketenes (146-148) was reported by Moore and co-workers. 190 The reaction proceeds via a thermal rearrangement (Schemes [33][34][35] (153). Electrocyclic ring opening of 153 gives the dienyl ketene (154) which then undergoes sixelectron electrocyclization followed by enolization to yield a phenol (155).…”
Section: Miscellaneous Synthesis Of 14-benzoquinones From Unique Prementioning
confidence: 99%
“…Kingston and co-workers 33 have isolated two new benzoquinones 2-methoxy-6-heptyl-1,4-benzoquinone (3) and 2-methoxy-6-pentyl-1,4-benzoquinone (4) from the leaves of Miconia lepidota present in Surinam forests. Both quinones 3 and 4 exhibited activity towards mutant yeast strains based on Saccharomyces cerevisiae, indicative of their cytotoxicity and potential antitumor activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 O gênero Miconia é ainda pouco conhecido com relação ao seu potencial químico. Das espécies até então investigadas foram isoladas benzoquinonas, 4 triterpenos, [5][6][7][8][9] flavonoides, [10][11][12] compostos fenólicos e taninos. 13 Poucas são as referências à trabalhos de investigação sobre os metabólitos de Miconia ferruginata.…”
Section: Introductionunclassified